Kantian Courage:Advancing the Enlightenment in Contemporary Political Theory : Advancing the Enlightenment in Contemporary Political Theory - Tampio, Nicholas (Book collections on Project MUSE., 2012)
"Advancing the Enlightenment draws upon John Rawls, Gilles Deleuze, and Tariq Ramadan to present a vision for progressive politics. Rather than defend Kant's ideas, heirs of the Enlightenment should create concepts such as overlapping consensus, rhizome, and space of testimony to facilitate alliances across religious and philosophical differences"--